Language Acquisition and Language Teaching Methods in English as a Foreign Language (EFL) Context: A Literature Review Study - Urip Sulistiyo (JAMBI-ENGLISH LANGUAGE TEACHING, 2017)
Abstract This article reports on a systematic review of language acquisition and language teaching methods in EFL context. The theory of Language Acquisition proposed by Krashen (1982) was reviewed and elaborated with other relevant literature such as language learning theory and language teaching methods in this study. Some insights regarding second/foreign language classroom practice, the role of teachers in EFL language classrooms, and language teaching methods were also reviewed to give snapshots about English teaching and learning practice in English as a foreign language context. Keywords: EFL, Language Acquisition, Language Learning, Language Teaching